1995
DOI: 10.1007/bf02110008
|View full text |Cite
|
Sign up to set email alerts
|

ATPase activity, IF1 content, and proton conductivity of ESMP from control and ischemic slow and fast heart-rate hearts

Abstract: Earlier studies by Rouslin and coworkers showed that, during myocardial ischemia in slow heart-rate species which include rabbits and all larger mammals examined including humans, there is an IF1-mediated inhibition of the mitochondrial ATPase due to an increase in the amount of IF1 bound to the ATPase (Rouslin, W., and Pullman, M.E., J. Mol. Cell. Cardiol. 19,661-668, 1987). Earlier work by Guerrieri and colleagues demonstrated that IF1 binding to bovine heart ESMP was accompanied by parallel decreases in ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Determination of mitochondrial concentrations of IF 1 show some species differences. Rouslin et al (24,26) grouped different species into several categories according to heart rate, IF 1 content, or IF 1 affinity. Larger animals (slow heart rate species) such as dogs express relatively higher amounts of IF 1 , although the study by Jennings et al (11) showed that during ischemia, inhibition of the ATP hydrolase activity was incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Determination of mitochondrial concentrations of IF 1 show some species differences. Rouslin et al (24,26) grouped different species into several categories according to heart rate, IF 1 content, or IF 1 affinity. Larger animals (slow heart rate species) such as dogs express relatively higher amounts of IF 1 , although the study by Jennings et al (11) showed that during ischemia, inhibition of the ATP hydrolase activity was incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the ATP hydrolase activity by IF 1 is reversible upon restoration of the mitochondrial electrochemical gradient and increased pH as might be seen during reperfusion (30). IF 1 may not play an important role in inhibiting ATPase activity in "fast" heart rate species such as the rat, where it is not as highly expressed compared with the dog and rabbit (23,24,26). Nevertheless, the unique feature of IF 1 is that it specifically inhibits ATP hydrolase activity rather than ATP synthetic activity, showing that it is possible to selectively inhibit hydrolase activity.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…IF-1 in the heart is expressed differently in several mammalian species, and this has been subdivided into "fast heart rate species" (rat, mice, and birds) that express low levels of IF-1 and "slow heart rate species" (dogs and rabbits) that express high levels of IF-1 [10,[47][48][49]. It is presently unclear how these differences can affect the pathogenesis of ischemia in the different species.…”
Section: If-1 Proteinmentioning
confidence: 99%